Hemoglobin and hematocrit during an 8 day mountainbike race: A field study - Wirnitzer, K. C.; Faulhaber, M. (Journal of Sports Science & Medicine, 2007)
The results of the present study reflect that fluid substitution was not effective enough to prevent exercise induced dehydration during E1 (Table 2). Thus, heat elimination by the redistribution of blood flow and body water losses due to sweat and respiration induced a PV decline leading to increased levels of Hb and Hct. (Convertino, 1991; Mounier et. al., 2003; Sawka et. al., 2000; Schmidt et. al., 2000; Schumacher et. al., 2000). In contrast to exercise induced short term effects this field study further points out a significant decline in Hb and Hct during the course of the TAC 2004. Additionally, decrease in Hct was not that markable in former publications as presented in this study: -5.1 % (Schmidt et. al., 2000) and -4.31 % (Mounier et. al., 2003). While long term decreases in Hb and Hct are pronounced, enhancement in PV is calculated not to reach statistical significance. Mounier et. al. (2003) found a similar PV expansion of 8.5 %. Although this field study was only performed on six subjects hemodilutive effects are clearly shown. Convertino, 1991, Fellmann et. al. (1999) and Sawka et. al. (2000) found that PV expansion was maximal on the fourth day of a 7-day ultra endurance race. Until E4 of the TAC 2004 Hb and Hct show a continuous and pronounced fall while PV expansion is pronounced. Hb and Hct readings remained nearly at this lower level while PV remained narrow to this higher level until the end of this MTB race. This field study was done under authentic conditions of the TAC 2004. The authors are absolutely conscious of the fact that method used is not gold standard. The decision had to be made in the light of several unexpected operational and organisational difficulties in participation and accomplishment of this huge 8 days lasting MTB race. It can be concluded that during E1 of the TAC 2004 hemoconcentration was detected to be the acute effect of strenuous endurance impact on hematological parameters. Furthermore, hemodilution was shown as a long term effect of repeated MTB endurance strains.